Joint Educational Programs of Russia and China: Status and Problems of Implementation - T. L. Guruleva (Moscow Polytechnic University, 2019)
The article focuses on the current state and the problems concerning implementing joint educational programs by Russia and China. The author dwells on the concept of the joint educational program, proposes a classification of joint educational programs, including joint degree programs (joint diploma), double degree programs (double diplomas), and the program of included training. The analysis of visiting Russian-Chinese and inbound Sino-Russian joint educational programs as at 2018 was carried out. The problems and obstacles of joint educational programs implementation by Russia and China are revealed, among which are: legislation problems, problems of the language of instruction, problems of the cost of education, the necessary information support. The most serious problems relate to the legislation. First of all, it is the uncertainty concerning the meaning of the term "joint educational program" in the legislation framework. The attendant problems are licensing and accreditation of joint programs, award of diplomas, asymmetry between the number of visiting and inbound programs. The author comes to a conclusion that the legislation framework in the sphere of joint educational programs should include the following items: enrolment rules for foreign students in Russian universities; mechanisms of recognition of mobility periods and credits transfer for foreign participants of joint programs, migration rules of short-term courses.